2010
DOI: 10.1373/clinchem.2009.133876
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Gene Expression Analysis for Prediction of Postoperative Sepsis

Abstract: BACKGROUND:Postoperative sepsis is one of the main causes of death after major abdominal surgery; however, the immunologic factors contributing to the development of sepsis are not completely understood. In this study, we evaluated gene expression in patients who developed postoperative sepsis and in patients with an uncomplicated postoperative course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Moreover, in addition to other studies, these results highlight the potential of using transcriptomic biomarkers in the clinic [18]. The utility of such biomarkers lies in their capacity to provide timely information beyond that which is readily available from routine physiologic data and clinical examination.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, in addition to other studies, these results highlight the potential of using transcriptomic biomarkers in the clinic [18]. The utility of such biomarkers lies in their capacity to provide timely information beyond that which is readily available from routine physiologic data and clinical examination.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, CD3 expression on T lymphocytes was reduced in septic shock patients in comparison with healthy volunteers [34]. Similar decreased expression was observed at the mRNA level in patients developing sepsis or severe sepsis postoperatively [35] and in trauma patients [36]. Finally, CD28 expression (delivering a positive co-signal after ligation to B7.1 or B7.2) was depressed in trauma patients' anergic T cells and may contribute to incomplete activation of these cells [36].…”
Section: Discussionmentioning
confidence: 80%
“…This is consistent with a study in which investigators observed lower perioperative IL1B expression in patients who subsequently developed postoperative sepsis. [30] Second, IL2RB (22q13.1) encodes the beta subunit of the interleukin-2 receptor. It is expressed by lymphocytes and by binding with interleukin-2 (IL-2) leads to T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%